Media literacy: The case of the Catholic clergy in Portugal - Fandos, Manuel; Lopes Neto, Miguel; Côrtes-Moreira, Sandra; Gadea, Walter-Federico (Anàlisi, 2024)
Using data obtained from a random sample of the Catholic clergy in Portugal, consisting of 546 Portuguese priests from all the country’s dioceses – representing almost 24% of the total – the concept of a networked society (timelessness and virtuality) is linked to concepts of community and Christian identity, identifying how digital technologies, the media and social networks – the internet in general – are involved in their expression. It then describes what digital media the clergy use and how they use them in their pastoral and ministerial practice, as well as their opinion of their potential in ministerial activity, according to the data obtained through a survey carried out for this purpose. Some of the points identified as necessary to improve the presence and missionary performance of Portuguese Catholic priests in the digital world are: training that results in better digital literacy; an adaptation of language and its appropriate use in the different types and formats of digital environments; and less info-exclusion. Some lines of research are suggested, which point out how to improve the educommunication of the clergy, their media literacy and their relationship with the world of digital communication.